Synodality, a path of community conversion - Becquart, Nathalie (Razón y fe, 2021)
Synodality is a path of discernment in common, listening to the Spirit. It is a call to personal, communitarian and ecclesial conversion. It is also a path of spiritual and pastoral conversion. Therefore, synodality supposes and demands spiritual attitudes for its implementation, which could be summarized in a spirituality of the “ecclesial we” that has as its objective the construction of a people, a fraternal and missionary ecclesial community at the service of the common good of society. In this article we would like to offer some reflections to help us understand synodality as a process of conversion that invites us to learn the art of discernment in order to walk together in the Church.
Keywords: synodality; pastoral conversion; ecclesial conversion; discernment; spirituality; Church